2010
DOI: 10.1111/j.1600-0404.2010.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway limitation and exercise intolerance in well-regulated myasthenia gravis patients

Abstract: Well-regulated MG patients, especially those using pyridostigmine, tend to have an airway obstruction. The modest airway limitation might be a contributing factor to their fatigue. Patients who are not using acetylcholinesterase inhibitor seem to have diminished exercise endurance in spite of their clinically complete remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Medication can influence both fatigue and autonomic functions. We concluded in a previous study that well-regulated MG patients with fatigue showed an obstructive pattern in pulmonary function tests and this was more pronounced in patients using AChEI [23]. Sixty one per cent (50/82) of the MG patients in our study used AChEI, which is suspected to alter autonomic functions, but we did not find that use of AChEI was an independent explanatory variable, although patients using them had slightly higher total fatigue scores than controls (mean ± SD: 15.0 ± 6.2 vs 13.8 ± 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…Medication can influence both fatigue and autonomic functions. We concluded in a previous study that well-regulated MG patients with fatigue showed an obstructive pattern in pulmonary function tests and this was more pronounced in patients using AChEI [23]. Sixty one per cent (50/82) of the MG patients in our study used AChEI, which is suspected to alter autonomic functions, but we did not find that use of AChEI was an independent explanatory variable, although patients using them had slightly higher total fatigue scores than controls (mean ± SD: 15.0 ± 6.2 vs 13.8 ± 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are a few case reports, but none have described MG deterioration from physical activity, as well as a few studies on respiratory muscle training . Nevertheless, another study indicated exercise intolerance in well‐regulated MG patients . The benefits of physical exercise are well known, and general recommendations regarding physical activity are available for healthy adults .…”
mentioning
confidence: 99%
“…This was more marked in patients on acetylcholine esterase inhibitors (Elsais et al, 2010). In myasthenic crisis, bronchodilators may be useful in maintaining airway patency and overcoming bronchospasm.…”
Section: Bronchodilator Therapymentioning
confidence: 91%